Sei sulla pagina 1di 5

Georg Noldeke¨

Herbstsemester 2012

Advanced Economic Theory Hints for Problem Set 2

1. Properties of the Cobb-Douglas Production function:

(a)

(b)

The Cobb-Douglas production function is homogenous of degree α + β. This is demonstrated by the following calculation:

 f (tx 1 , tx 2 ) = = = =

A(tx 1 ) α (tx 2 ) β

At α x α t β x β

1

2

t α+β Ax α x β

2

1

t α+β f(x 1 , x 2 ).

To verify strict concavity, it suﬃces to show that the Hesse matrix is negative deﬁnite. To obtain the Hesse matrix, we ﬁrst calculate the partial derivatives (the ﬁnal equalities will serve to simplify subsequent calculations):

∂f(x 1 , x 2 )

∂x ∂f(x 1 , x 2 )

1

x 2

=

αAx α1 x β

1

2

= βAx α

1

x

β1

2

=

=

α 1 f(x 1 , x 2 )

x

β 2 f(x 1 , x 2 )

x

and then calculate the second-order partial derivatives (the ﬁrst equality in each line just introduces a more convenient notation):

2 f(x 1 , x 2 )

f

∂x 2 = 2 f(x 1 , x 2 )

∂x 2 = 2 f(x 1 , x 2 )

f

∂x 1 ∂x 2 f 21 = 2 f(x 1 , x 2 ) ∂x 2 ∂x 1

11

f 22

12

=

1

2

=

α(α 1)Ax α2 x β

1

2

= β(β 1)Ax α

1

x

β2

2

=

=

αβAx α1

1

αβAx α1

1

x

x

β1

2

β1

2

α(α 1)

= f(x 1 , x 2 )

2

x

1

β(β 1)

= f(x 1 , x 2 )

x

2

2

αβ

x 1 x

2

αβ

= f(x 1 ,

x 1 x

2

=

f(x 1 , x 2 )

x 2 )

For strict concavity two properties are needed:

f 11 < 0.

f 11 f 22 f 12 f 21 > 0. The ﬁrst condition is satisﬁed for 0 < α < 1. Because we have assumed that α > 0, β > 0 and α + β < 1 holds, this condition is satisﬁed. To verify the second condition, we calculate:

f 11 f 22 f 12 f 21 = α(α 1)β(β 1) α 2 β 2 f(x 1 , x 2 ) x 1 x 2

2

.

This expression is strictly positive whenever the expression in square brackets is strictly positive. As we have

α(α 1)β(β 1) α 2 β 2 = αβ (1 α β) ,

and the right side of this equality is strictly positive when α > 0, β > 0 and α + β < 1 holds, this ﬁnishes the proof.

1

(c)

The following properties need to be checked:

f (0, 0) = 0.

f is strictly increasing.

f is strictly quasiconcave.

The ﬁrst of these should be obvious (f (0, 0) = A·0 α ·0 β = A·0·0 = 0). The second is implied by the fact that the partial derivatives of f (·) are strictly positive (see above). To establish the third property, we can ﬁrst observe that we have already estab- lished that every Cobb-Douglas production function with α + β < 1 is strictly concave and, thus, strictly quasiconcave. Hence, it remains to consider the case α + β 1. For this case observe that we can rewrite the production function as

˜

f(x 1 , x 2 ) = A f(x 1 , x 2 ) α+β+1 ,

where

˜

f(x 1 , x 2 ) = x α/(α+β+1) x β/((α+β+1)

˜

1

2

.

The function f (·) is a Cobb-Douglas production function with exponents that sum

to less than one. Hence, it is strictly concave and, thus, strictly quasiconcave. As

˜

f (·) is a positive monotonic transformation of f(·) 1 it follows that f (·) is strictly

quasiconcave 2 ﬁnishing the argument.

2. Cost Minimizaton and Duality:

(a) To derive the cost function for the Cobb-Douglas production function, we need to consider the cost minimization problem. The Lagrangian for this problem is

L(x 1 , x 2 , λ) = w 1 x 1 + w 2 x 2 λ [f(x 1 , x 2 ) y] .

The corresponding Lagrange conditions are

w 1 λαAx α1 x β = 0

= 0

w 2 λβAx α

1

2

1

x

β1

2

y

Ax α x β = 0.

1

2

It will prove to be a good idea to rewrite these equations as 3

αλy =w 1 x 1

βλy =w 2 x 2

y

=Ax α x β 2 .

1

1 See Theorem 1.2 in the textbook for the deﬁnition of a positive monotonic transformation.

2 This is easy enough to check from the deﬁnition of strict quasiconcavity. Alternatively, the result follows

˜

from Theorems 1.2 and 1.3 in the textbook. Viewing f (·) as a utility function, the second part of Theorem 1.3

˜

f (·) represents a strictly convex preferences relation. As a positive monotonic transformation

of f (·) the function f (·) represents the same preference (Theorem 1.2).

statement in the second part of Theorem 1.3 it follows that f (·) is strictly quasiconcave. 3 To obtain the ﬁrst of the following equations multiply the ﬁrst equation above by x 1 and then observe

implies that

Using the other direction of the

˜

that the term multiplying α is equal to Ax α x β is analogous.

1

2

= y. The argument for the second of the following equations

2

The minimal cost of producing output y is given by w 1 x 1 + w 2 x 2 where (x 1 , x 2 ) (together with λ) is the solution to the Lagrange conditions. As we know that the solution to the Lagrange condition satisﬁes the ﬁrst two of the above equations we know that the cost function is given by

c(w 1 , w 2 , y) = w 1 x 1 + w 2 y 2 = (α +

β) λy.

(1)

Hence, to determine the cost function we only need to determine the value of λ. Solving the ﬁrst two of the rewritten Lagrange conditions for

x 1 = αλy

w

1

and x 2 = βλy

w

2

and substituting the result into the third of these conditions yields:

y

=

A αλy α βλy

w

1

w

2

β

Solving this equation for λ yields: 4

λ = w 1

α

α/(α+β) w 2

β

β/(α+β) A (1/(α+β)) y (1αβ)/(α+β) .

Substituting this value for λ into (1) we obtain the cost function as

c(w 1 , w 2 , y) = Bw γ

1 w

 where = 1/(α + β), γ = and

α

α + β ,

δ

2

y

δ =

β

α + β

B = A 1/(α+β) (α + β)α α/(α+β) β β/(α+β) .

(2)

(3)

(4)

 (b) As a function of (w 1 , w 2 ) the cost function in (2) has the same functional form as the Cobb-Douglas production function. Because the parameters γ and δ satisfy γ > 0, δ > 0 and γ + δ = 1, the calculations from Problem 1 (b) show that the Hesse matrix of the second order partial derivatives with respect to (w 1 , w 2 ) is negative semi-deﬁnite. This implies that the cost function is concave in (w 1 , w 2 ). (c) Given a cost function as in (2), we can use (3) to determine the parameters of the underlying Cobb-Douglas production function as

α = γ/ and β = δ/ .

4 Write the above equation as

where

˜

Dividing both sides by Ay α+β yields

implying

˜

λ =

y =

Aλ ˜ α+β y α+β ,

A = A

˜

1 α

α

w

2 β

β

w

λ α+β =

A 1 y 1αβ ,

˜

.

A ˜ 1/(α+β) y (1αβ)/(α+β) .

Replacing A by the expression from above yields the following equation.

3

Once α and β are known, for any given value of B we can solve (4) to detemine

A. 5

3. Proﬁt Maximization and Duality:

(a)

To simplify notation when considering the proﬁt maximization problem (in which the focus is on the optimal choice of y) write the cost function as

c(w 1 , w 2 , y) = c(w 1 , w 2 , 1)y ,

where

c(w 1 , w 2 , 1) = Bw γ w

1

δ

2 .

The ﬁrst order condition for the proﬁt maximization problem 6 is

p = c(w 1 , w 2 , 1)y 1 .

(5)

Solving this condition for y yields the output supply function

y(p, w 1 , w 2 ) = ( c(w 1 , w 2 , 1)) 1/(1 ) p 1/( 1) .

The proﬁt function is given by

π(p, w 1 , w 2 ) = py(p, w 1 , w 2 ) c(w 1 , w 2 , 1) (y(p, w 1 , w 2 )) .

(6)

Rather than ﬁrst substituting y(p, w 1 , w 2 ) into this expression and then simplify- ing, a better approach is to observe that we can use (5) to rewrite (6) as follows:

 π(p, w 1 , w 2 ) = c(w 1 , w 2 , 1) (y(p, w 1 , w 2 )) − c(w 1 , w 2 , 1) (y(p, w 1 , w 2 )) = ( − 1) c(w 1 , w 2 , 1) (y(p, w 1 , w 2 )) Substituting y(p, w 1 , w 2 ) = ( c(w 1 , w 2 , 1)) 1/(1− ) p 1/( −1) into this expression and

(b)

simplifying yields:

π(p, w 1 , w 2 ) = (

1)

= ( 1)

/(1 ) c(w 1 , w 2 , 1) 1+ /(1 ) p /( 1)

/(1 ) c(w 1 , w 2 , 1) 1/(1 ) p /( 1)

Hotelling’s lemma states the the input demand functions are given by

x i (p, w 1 , w 2 ) = π(p, ∂w w 1 i , w 2 ) .

Using the expression for the proﬁt function obtained in the previous problem, the relevant partial derivative of the proﬁt function can be determined (use the chain rule!) as

∂π(p, w 1 , w 2 )

∂w i

=

/(1 ) c(w 1 , w 2 , 1) /(1 ) p /( 1) c(w 1 , w 2 , 1)

∂w i

5 I don’t give the formula for A here as it is not important. What is important is the idea that the parameters of the production technology can be determined from the parameters of the cost function. 6 The assumption α + β < 1 ensures that objective function in the proﬁt maximization problem is strictly concave in y, implying that the solution to the ﬁrst order condition is indeed the proﬁt maximizing output.

4

Recalling that c(w 1 , w 2 , 1) = Bw γ w

1

δ

2

we can calculate

∂c(w 1 , w 2 , 1)

∂w 1 ∂c(w 1 , w 2 , 1)

∂w 2

=

γBw γ1 w

1

δ

2

= δBw γ w

1

δ1

2

to obtain the input demand functions as

x 1 (p, x 2 (p,

w 1 , w 2 ) =

/(1 ) c(w 1 , w 2 , 1) /(1 ) p /( 1) γBw γ1

1

w

δ

2

δ1

2

w

1

w 1 , w 2 ) = /(1 ) c(w 1 , w 2 , 1) /(1 ) p /( 1) δBw γ

.

(c) Recalling the functional form of the proﬁt function,

π(p, w 1 , w 2 ) = ( 1) /(1 ) c(w 1 , w 2 , 1) 1/(1 ) p /( 1) ,

it should be clear that can be determined by considering how the proﬁt changes with the output price. Once is determined, the unit cost function c(w 1 , w 2 , 1) can be determined by considering how the proﬁt changes with w 1 and w 2 . Hence, we can infer the parameters A, , γ, and δ of the cost function from the proﬁt function. The parameters of the production function can then be recovered from the parameters of the cost function.

5